(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2021)
The article refers to the enrichment of vocabulary in children of the third year of life, through the use of didactic games, since Early Childhood is the period where the initial training of children takes place, with it the need for communication. To solve this problem, it is proposed to develop educational games to enrich vocabulary in children of the third year of life, they are used as a work alternative for educators. The understanding and richness of active language, the considerable increase in vocabulary and an intense assimilation of the grammatical aspect of the language, causes the real possibility of establishing adequate verbal communication. The research was carried out at the “Somos Felices” kindergarten, in the Bayamo municipality. For its development, theoretical methods were used: analytical - synthetic, inductive - deductive and modeling; empirical method: observation, which allowed the children, in addition to acquiring knowledge, to develop skills of utmost importance for their development that will be present throughout their lives.